2008
DOI: 10.1542/peds.2006-3673
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Effectiveness of Screening for Scoliosis: A Case-Control Study

Abstract: OBJECTIVE. The aim of this study was to test the hypothesis that screening for scoliosis is effective in reducing the need for surgical treatment. METHODS. The study was a case-control study. A total of 125 consecutive patients who were treated surgically for idiopathic scoliosis between January 2001 and October 2004 and who were born on or after January 1, 1984, were invited; 108 agreed to participate. A total of 216 control subjects were selected randomly and anonymously, matched with respect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 20 publications
1
17
0
1
Order By: Relevance
“…However, the sensitivity and specificity of scoliosis screening depends on the experiences of the examiner. Therefore, the effectiveness of scoliosis screening is still under dispute [38][39][40][41][42]. Moreover, the screening could increase exposure to radiographs because the radiography is required to officially diagnose scoliosis for positive findings of a rib hump [42].…”
Section: Discussionmentioning
confidence: 99%
“…However, the sensitivity and specificity of scoliosis screening depends on the experiences of the examiner. Therefore, the effectiveness of scoliosis screening is still under dispute [38][39][40][41][42]. Moreover, the screening could increase exposure to radiographs because the radiography is required to officially diagnose scoliosis for positive findings of a rib hump [42].…”
Section: Discussionmentioning
confidence: 99%
“…Spo strze że nia po wy ższe po twier dza ją ba da nia Bunge, któ ry po przez re tro spek tyw ną ana li zę wy wia du od osób ope ro wa nych z po wo du sko lio zy wy ka zał, że ba da nie prze sie wo we w wie ku 11-14 lat wy ko na no tyl ko u 32,8% osób ope ro wa nych z po wo du bocz ne go skrzy wie nia krę go słu pa. Na to miast u 43,4% ope ro wanych nie wy ko ny wa no wcze śniej ba da nia prze sie wowe go [23].…”
Section: Discussionunclassified
“…Some studies concluded that SSS is effective, whereas others questioned the effectiveness or even considered such screening to be unethical [23] . Arguments against screening are as follows: (1) low predictive value leading to excessive number of children referred to specialists; (2) possibly increased amount of x-ray imaging in children; (3) lack of certainty about which instance of small scoliosis (Cobb angle < 20°) will progress and require treatment; (4) cost issue and (5) stress induced by examination [6] .…”
Section: Position On Sssmentioning
confidence: 99%
“…Bunge et al [23] performed a case-control study estimating the effectiveness of SSS in the Netherlands. Their results showed no evidence that SSS using the FBT reduced the need for surgery.…”
Section: Status Of Sss In the Worldmentioning
confidence: 99%